ANALYSIS OF MARKETING STRATEGIES THROUGH THE UNIQUENESS OF YOGYA’S HERITAGE, CULTURES, AND CULINARY PRODUCTS AS AN ASSET OF BRANDING TOWARDS TOURISM DEVELOPMENT IN YOGYAKARTA SPECIAL REGENCY - Isdarmanto Isdarmanto; Dwiyono Rudi Susanto; Dyah Wahyuning Tyas; Sumiyar Mahanani; Farah Diana Djamil (Pringgitan, 2021)
Yogyakarta's tourism potential from asset uniqueness and heritages is a major factor in tourism development in Yogyakarta. This is a responsibility that must be realized by all stakeholders of tourism so that tourism assets uniqueness of ancestral heritage in Yogyakarta becomes a tourist attraction as a capital of local wisdom in the concept of branding city of Yogyakarta. The participation of communities and local governments in managing sustainable tourism development programs is also an important aspect to develop of a new brand city of Yogyakarta. There is limited public awareness of the existence of excellence asset heritages of Yogyakarta which is a selling point in branding the city. This study aims to identify and know the role of branding through the cultural heritage of Yogyakarta cultures and culinary products in marketing strategy to the development of tourism in Yogyakarta. This research use qualitative research that can focus on the problems encountered, as well as with a process methodology that illustrates how qualitative training can provide many uses and benefits for more effective and in-depth research. The fact is that the numbers of foreign tourists who visit the tourism site still do not meet the expected target compared to the number of domestic tourists. Therefore it is necessary to research and empower the community to be able to change the mindset & to have more concern to provide positive supports for Yogyakarta tourism development so that it is more competitive in global competition.Keywords: Uniqueness, Heritage, Culture, Tourism Development